Milton, evil and literary history - Colebrook, Claire (Continuum literary studies., 2008)
Milton, Evil and Literary History addresses the ways in which we read literary history according to quite specific images of growth, development, progression, flourishing and succession.€ Goodness has always been aligned with a life of expansion, creation, production and fruition, while evil is associated with the inert, non-relational, static and stagnant.€ These associations have also underpinned a distinction between good and evil notions of capitalism, where good exchange enables agents to enhance their living potential and is contrasted with the evils of a capitalist system that.